Utilization of Kuda Lumping Culture in Reducing Cancer Stigma in Society - Sri Ananingsih, Esti; Kusumawaty, Ira; Yunike, Yunike; Elfrida, Solha; M, Monalisa; Inastyarikusuma, Tarrinni; Podojoyo, Podojoyo (Yayasan Rumah Ilmu Professor, 2024)
Stigma towards cancer is still a significant problem in many communities, including in Indonesia, so it often hampers efforts for early detection, treatment and social support for cancer sufferers. This research aims to explore the use of local culture, especially the Kuda Lumping art, in reducing the stigma of cancer in society. Kuda Lumping was chosen because it is a popular traditional performing art and has a strong appeal among the community. This research method uses a qualitative approach with a case study design. Data was collected through in-depth interviews, participant observation, and surveys of 7 respondents involved in the Kuda Lumping-based education program in Pangkalan Benteng Village. This program involves the Kuda Lumping performance which includes educational messages about cancer, the importance of early detection, and social support for cancer sufferers. The research results show that the integration of health messages in the Kuda Lumping show can effectively reduce the stigma of cancer. Most respondents reported an increase in understanding of cancer and a decrease in negative attitudes towards cancer sufferers after watching the show. In addition, the use of symbols and narratives familiar to the local community makes the message easier to receive and understand. Education through Kuda Lumping also increases community involvement in efforts to prevent and detect cancer early. This research concludes that local cultural approaches such as Kuda Lumping have great potential in overcoming cancer stigma. Traditional art performances combined with health messages can reach various levels of society effectively and convey important information in an engaging and relatable way. Governments and health organizations are encouraged to consider using local arts in public health education programs. This step will not only help reduce stigma but also strengthen community involvement in cancer prevention and treatment efforts.